HUBUNGAN POWER OTOT LENGAN DAN BAHU KOORDINASI MATA – TANGAN TERHADAP KETEPATAN HASIL SERVICE ATAS PADA CLUB PUTRA CENDANA DUMAI - Amelia, Siska; Saripin, Saripin; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The problem in this research is there are athletes who are the exactness of the service it is still less than maximum. It was seen when athletes doing the game, a the service to strain on the net and sometimes directionless the box the line of the field. The objective in this study is to identify how the power arm muscles and shoulders the coordination of eye- hand against the precision of the service of the club the men Cendana Dumai. The population in this study are all athletes at club, the men Cendana Dumai, amounting to 17 people. The sampling of the whole population (the total sampling). Instrument is used in this study is two hand medicine Ball put, test the coordination of the eye and hand, test service for volley bal. The data obtained in the analysis with using a tehnique the correlation of the double. Based on the results of research and data processing, it can be concluded that for the correlation between variables x1 x2 with variabel and by the value of r=0.726 the rx1x2y > end table (0.726>0.482) the Ha received, in other words there is a power arm muscles and shoulders, eye- hand coordination of the exactness of the service on club the Cendana Dumai.Keywords : Power the shoulder, eye – hand coordination, service for beach volleyball